STUDY ON THE EFFECTIVENESS OF MUNICIPAL SOLID WASTE (MSW) PROCESSING IN THE REFUSE DERIVED FUEL (RDF) PRODUCTION PROCESS (CASE STUDY: RDF PLANT JERUKLEGI) - Resti Aisyarah, Nidha
Refuse-Derived Fuel (RDF) Plant Jeruklegi has become a facility at TPA Tritih Lor, utilizing waste-to-energy (WtE) technology to convert waste into alternative fuel. TPA Tritih Lor is the largest landfill service area and capacity in Cilacap Regency. Consequently, an effectiveness study is necessary to optimize RDF Plant Jeruklegi. Based on sampling, the most prevalent composition is organic waste, accounting for 43%. The density of the incoming waste is 301.49 kg/m³. The RDF production process involves mechanical biological treatment (MBT), including weighing, sorting by scavengers, shredding, drying, and separation using a screening machine. The drying process is conducted in a drying bay equipped with semipermeable membranes and an aeration unit to support microbial degradation. The RDF Plant can produce RDF with a moisture content of 12.264%, ash content of 8.483%, volatile content of 75.831%, fixed carbon content of 3.422%, particle size less than 5 cm, calorific value of 4634.116 kcal/kg, mass reduction of 67.67%, and volume reduction of 72.57%. The sorting process by scavengers has the potential to reduce the calorific value of the waste by up to 3.49%. The use of RDF Plant can extend the landfill's lifespan by 8 years and 10 months and prevent 18,354.36 tons of CO?eq per year. The RDF Plant still requires operational costs of IDR226,442 per ton of waste and investment is crucial for its feasibility. The drying process requires 44 days to optimize the quality of the produced RDF.